Advertisement Remove all ads

Simplify the Following Expressions: (3 + Sqrt3)(3 - Sqrt3) - Mathematics

Simplify the following expressions:

`(3 + sqrt3)(3 - sqrt3)`

Advertisement Remove all ads

Solution

We know that `(a - b)(a + b) = a^2 - b^2`. We will use this property to simplify the expression

`(3 + sqrt3)(3 - sqrt3)`

`∴ (3 + sqrt3)(3 - sqrt3) = (3)^2 - (sqrt3)^2`

`= 3^2 - sqrt3 xx sqrt3`

`= 3 xx 3 - sqrt(3 xx 3)`

`= 9 - (3^2)^(1/2)`

`= 9 - 3^1`

= 6

Hence the value of expression is 6.

 

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Mathematics for Class 9
Chapter 3 Rationalisation
Exercise 3.1 | Q 3.4 | Page 2
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×